2020
DOI: 10.1063/1.5138902
|View full text |Cite
|
Sign up to set email alerts
|

A comparative first-principles investigation on the defect chemistry of TiO2 anatase

Abstract: Understanding native point defects is fundamental in order to comprehend the properties of TiO 2 anatase in technological applications. Several first-principles studies have been performed in order to investigate the defect chemistry of this material. The reported values are, however, scattered over a wide range. In this manuscript we perform a comparative study employing different approaches based on semilocal, DFT+U and screened hybrid functionals in order to investigate the dependence of defect properties, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…The convergence criteria of energy, maximum force, maximum stress, and maximum displacement are 1×10 − 5 eV/atom, 0.03 eV/Å, 0.05 GPa, and 0.001 Å, respectively. The optimized anatase TiO 2 lattice parameters are a = b = 3.79 Å and c = 9.77 Å, which are consistent with the previous experimental and theoretical results [31][32][33]. In this work, a (1 × 4) anatase (101) surface supercell was used as the slab model with three O-Ti-O layers, and the underlying O-Ti-O layer was xed to simulate the bulk atomic structure, as shown in Fig.…”
Section: Computational Methods and Modelssupporting
confidence: 80%
“…The convergence criteria of energy, maximum force, maximum stress, and maximum displacement are 1×10 − 5 eV/atom, 0.03 eV/Å, 0.05 GPa, and 0.001 Å, respectively. The optimized anatase TiO 2 lattice parameters are a = b = 3.79 Å and c = 9.77 Å, which are consistent with the previous experimental and theoretical results [31][32][33]. In this work, a (1 × 4) anatase (101) surface supercell was used as the slab model with three O-Ti-O layers, and the underlying O-Ti-O layer was xed to simulate the bulk atomic structure, as shown in Fig.…”
Section: Computational Methods and Modelssupporting
confidence: 80%
“…We have recently shown that DFT+U , which is computationally much less demanding, is able to yield geometric structures in good agreement with those obtained with hybrid functionals [56]. The agreement of the defect formation energy is considerably worse: using DFT+U , we found that the simple vacancy configuration has energy 0.77 eV larger than the split vacancy, while using HSE, this difference is of about 0.38 eV [56]. In both cases these minima are however clearly distinguishable.…”
Section: The Neutral O In Tio 2 Anatasementioning
confidence: 53%
“…Simply removing an oxygen atom from the host material and relaxing the atomic positions typically leads to the "simple" vacancy to the inability of standard DFT to treat strongly localized electrons, the split configuration is most prominent using either the DFT+U approach or hybrid functionals. We have recently shown that DFT+U , which is computationally much less demanding, is able to yield geometric structures in good agreement with those obtained with hybrid functionals [56]. The agreement of the defect formation energy is considerably worse: using DFT+U , we found that the simple vacancy configuration has energy 0.77 eV larger than the split vacancy, while using HSE, this difference is of about 0.38 eV [56].…”
Section: The Neutral O In Tio 2 Anatasementioning
confidence: 56%
“…This reaction is directly analogous to what has been proposed for iron by Wilson et al [3] At high temperatures, vacancy condensation was directly observed in transmission electron microscopy, [48] which may also play a role under the conditions in this work. Thermodynamic defect levels for the different dominating defects in anatase TiO 2 are available in the literature, [49,50] and more recent literature also discussed the differences obtained in previous calculations. [50] As dissolution occurs from the surface, special surface or subsurface defects as suggested from density functional theory calculations [51] may be crucial in the predominant dissolution channels.…”
Section: The Role Of Electron-hole Pair Formationmentioning
confidence: 99%